2010
DOI: 10.4238/vol9-3gmr833
|View full text |Cite
|
Sign up to set email alerts
|

Association of the PPARγ2 gene Pro12Ala variant with primary hypertension and metabolic lipid disorders in Han Chinese of Inner Mongolia

et al.

Abstract: ABSTRACT. In order to determine whether Pro12Ala polymorphism of the peroxisome proliferator-activated receptor g2 (PPARg2) gene contributes to susceptibility to primary hypertension and metabolic lipid disorders, 482 unrelated subjects from Inner Mongolia were studied, including 137 healthy normotensive (controls) and 345 hypertensive subjects. PCR-RFLP was used to determine the genotypes of Pro12Ala variants of the PPARg2 gene, and direct sequencing was used to check the results. The frequency of the Ala all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
3
16
1
Order By: Relevance
“…Family aggregation of hypertension in Mongolians suggests that genetic factors might play an important role in the etiology of hypertension in Mongolians. Our previous study confirmed that the chloride channel Kb gene, CLCNKB, and the PPARγ gene are involved in the genetic susceptibility to hypertension in Mongolians (Gao et al, 2010;Su et al, 2012). Furthermore, in a small study of 385 unrelated Mongolians (158 patients with hypertension vs 227 normotensive subjects), we previously examined the association of the SLC12A3 gene with hypertension in Mongolians using nine tagSNPs of the SLC12A3 gene (rs6499858, rs2289119, rs13306673, rs2010501, rs7188995, rs7204044, rs4784733, rs8063406, and rs2304478) (Chang et al, 2011b).…”
Section: Discussionsupporting
confidence: 51%
“…Family aggregation of hypertension in Mongolians suggests that genetic factors might play an important role in the etiology of hypertension in Mongolians. Our previous study confirmed that the chloride channel Kb gene, CLCNKB, and the PPARγ gene are involved in the genetic susceptibility to hypertension in Mongolians (Gao et al, 2010;Su et al, 2012). Furthermore, in a small study of 385 unrelated Mongolians (158 patients with hypertension vs 227 normotensive subjects), we previously examined the association of the SLC12A3 gene with hypertension in Mongolians using nine tagSNPs of the SLC12A3 gene (rs6499858, rs2289119, rs13306673, rs2010501, rs7188995, rs7204044, rs4784733, rs8063406, and rs2304478) (Chang et al, 2011b).…”
Section: Discussionsupporting
confidence: 51%
“…The novel finding of our study showing that adolescents carrying the variant allele Ala presented higher serum triacylglycerol and VLDL-C levels is consistent with literature reports for obese adults [26,27] and for adults with coronary artery disease [28]. High triacylglycerol levels are associated with cardiovascular events, as they are directly related to increasing concentrations of atherogenic particles of LDL-C and VLDL-C. High VLDL-C can aggravate dyslipidemia, because it competes with CM in the clearance regulated by lipoprotein lipase and its hepatic receptors [29].…”
Section: Discussionsupporting
confidence: 81%
“…The Pro12-to-Ala mutation in PPARγ has been studied in depth. This polymorphism is significantly associated with hypertension, although its association with insulin sensitivity is still controversial (Deeb et al, 1998;Altshuler et al, 2000;Ostgren et al, 2003;Rodriguez-Esparragon et al, 2003;Yliharsila et al, 2004;Lu et al, 2008;Gao et al, 2010). The investigated polymorphisms herein are all located in intronic regions, which could play a role in regulating the expression level of a gene.…”
Section: Discussionmentioning
confidence: 98%
“…The association of PPARγ polymorphisms with hypertension has been investigated in various populations (Douglas et al, 2001;Gouni-Berthold et al, 2005;Sookoian et al, 2005;Badii et al, 2008;Gallicchio et al, 2008;Dallongeville et al, 2009;Yoshida et al, 2009;Fan et al, 2010;Gao et al, 2010;Underwood et al, 2010;Shi et al, 2012). Given that the prevalence of hypertension is significantly different among races (Lackland et al, 2008), PPARγ was tested as a risk factor for hypertension in a Mongolian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation